Role of Interleukin-17 in Acute Pancreatitis - Li, Guanqun; Chen, Hongze; Liu, Liwei; Xiao, Peng; Xie, Yu; Geng, Xinglong; Zhang, Tao; Zhang, Yang; Lu, Tianqi; Tan, Hongtao; Li, Le; Sun, Bei (Frontiers in Immunology, 2021)
Acute pancreatitis (AP) is a leading cause of death and is commonly accompanied by systemic manifestations that are generally associated with a poor prognosis. Many cytokines contribute to pancreatic tissue damage and cause systemic injury. Interleukin-17 (IL-17) is a cytokine that may play a vital role in AP. Specifically, IL-17 has important effects on the immune response and causes interactions between different inflammatory mediators in the AP-related microenvironment. In this literature review, we will discuss the existing academic understanding of IL-17 and the impacts of IL-17 in different cells (especially in acinar cells and immune system cells) in AP pathogenesis. The clinical significance and potential mechanisms of IL-17 on AP deterioration are emphasized. The evidence suggests that inhibiting the IL-17 cytokine family could alleviate the pathogenic process of AP, and we highlight therapeutic strategies that directly or indirectly target IL-17 cytokines in acute pancreatitis.